Identifikasi Aktivitas Antibakteri Pada Bumbu Kuah Bugis Yang Di Jual Di Beberapa Tempat Di Kecamatan Kota Selatan Kota Gorontalo - Ahmad, Lisna; Une, Suryani; Mutsyahidan, Arif Murtaqi Akhmad; Datau, Firman; Ibrahim, Nur Fadilah; Dahlan, Mastin; Paputungan, Sugi Saputra; Jannah, Sandrina Izathul; Junus, Zilanya; Lodi, Sarmila; Makalalag, Anjely (Universitas Negeri Gorontalo, 2024)
One of Indonesia's specialties is kuah bugis, which is a mixture of various spices such as garlic, ginger, and so on. In the composition are ingredients as antibacterial naturally. For example, garlic has the potential to overcome disease. Antibacterial is a compound used to inhibit bacteria. Antibacterials are usually found in an organism as a secondary metabolite. The purpose of this study was to determine the inhibition of bugis sauce seasoning against the growth of Staphylococcus aureus bacteria. The method used in this practicum is Randomized Group Design (RAK) to identify antibacterial activity in bugis sauce seasoning sold in markets in Kota Selatan District by taking three samples in each of three different places, then conducting research after sampling. The results of this practicum in the inhibition zone test are different from each sample. The N1 sample showed a higher inhibition zone value of 17.65 mm (strong) than N2 and N3. Where N2 is the lowest level between N1 and N3 which is 15.03 mm (strong) and N3 has a value of 15.58 mm (strong).